2009
DOI: 10.1002/path.2563
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 4 is induced in hepatocellular carcinoma by hypoxia and promotes tumour progression

Abstract: Striking similarities exist between molecular mechanisms driving embryonic liver development and progression of hepatocellular carcinoma (HCC). Bone morphogenetic proteins (BMPs), particularly BMP4, have been proposed to regulate embryonic hepatic development. BMP expression has been observed in neoplasia but the expression and biological role of BMP4 in human HCC are unknown. We found increased BMP4 mRNA and protein in HCC cell lines and tissue samples compared to primary human hepatocytes and corresponding n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 45 publications
9
71
0
Order By: Relevance
“…Our data imply that BMP4 signaling through BMPR1A increases HCC tumorigenesis and should be considered as a potential therapeutic target for HCC. with BMP4 siRNA compared with cells treated with control siRNA (23). We also observed that BMP4 signaling stimulates HCC cell migration, possibly through the MEK/ERK signaling cascade.…”
Section: Bmpr1a-knockdown Hcc Cells Are Significantly Less Tumorigenisupporting
confidence: 53%
See 1 more Smart Citation
“…Our data imply that BMP4 signaling through BMPR1A increases HCC tumorigenesis and should be considered as a potential therapeutic target for HCC. with BMP4 siRNA compared with cells treated with control siRNA (23). We also observed that BMP4 signaling stimulates HCC cell migration, possibly through the MEK/ERK signaling cascade.…”
Section: Bmpr1a-knockdown Hcc Cells Are Significantly Less Tumorigenisupporting
confidence: 53%
“…In addition, BMP9 has been reported to promote ovarian cancer cell proliferation through an autocrine mechanism (22). In primary HCCs, BMP4 has been reported to be upregulated in cancerous liver tissues by hypoxia (23); however, there is insufficient details of the molecular mechanisms of BMP4 prooncogenic functions, with regard to HCC.…”
Section: Introductionmentioning
confidence: 98%
“…However, in a previous comparison of adjacent normal and tumor tissues from the stomach, liver and esophagus, BMP4 expression was higher in the tumor samples. 28,40,47 Notably, our normal and tumor tissue microarrays were truly independent samples and not paired unlike previous studies. In the case of four normal tissues (ie, colon, pancreas, thyroid and ovaries) where no BMP4 expression was detected, a subset of the corresponding tumor samples had strong granular BMP4 staining indicating increased BMP4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that BMP4 expression strongly correlates with high tumor grade [158]. The role of other BMPs in HCC has not yet been analyzed but it is tempting to speculate that other BMP ligands could also play a role in the hepatocarcinogenesis process.…”
Section: Bmps In Liver Carcinogenesismentioning
confidence: 99%